The Fos-Related Antigen 1–JUNB/Activator Protein 1 Transcription Complex, a Downstream Target of Signal Transducer and Activator of Transcription 3, Induces T Helper 17 Differentiation and Promotes Experimental Autoimmune Arthritis - Moon, Young-Mee; Lee, Seon-Yeong; Kwok, Seung-Ki; Lee, Seung Hoon; Kim, Deokhoon; Kim, Woo Kyung; Her, Yang-Mi; Son, Hea-Jin; Kim, Eun-Kyung; Ryu, Jun-Geol; Seo, Hyeon-Beom; Kwon, Jeong-Eun; et al. (Frontiers in Immunology, 2017)
Dysfunction of Th17 cells leads to chronic inflammatory disorders. STAT3 orchestrates the expression of proinflammatory cytokines and pathogenic cell differentiation from IL-17-producing Th17 cells. However, the pathways mediated by STAT3 signaling are not fully understood. Here, we observed that FRA1 and JUNB are directly involved in STAT3 binding to sites in the promoters of Fosl1 and Junb. Promoter binding increased expression of IL-17 and the development of Th17 cells. Overexpression of Fra1 and Junb in mice resulted in susceptibility to collagen-induced arthritis (CIA) and an increase in Th17 cell numbers and inflammatory cytokine production. In patients with rheumatoid arthritis (RA), FRA1 and JUNB were colocalized with STAT3 in the inflamed synovium. These observations suggest that FRA1 and JUNB are associated closely with STAT3 activation, and that this activation leads to Th17 cell differentiation in autoimmune diseases and inflammation.